„Preserve Position and Power“ (Bao Wei Quan) Chapter of The Luxuriant Dew of the Spring and Autumn Annals (Chunqiu Fanlu) - Buljan, Ivana (2010)
Ivana Buljan: „Preserve Position and Power“ (Bao Wei Quan) Chapter of The Luxuriant Dew of the Spring and Autumn Annals (Chunqiu Fanlu) The presentation will analyze chapter 20 of "The Luxuriant Dew of the Spring and Autumn Annals" (Chunqiu fanlu) which is called „Preserve Position and Power“ (Bao wei quan). This chapter, together with some other chapters, belongs to the literary unit of the text which is designated by some scholars (e.g. Sarah Queen) as „Huang-Lao chapters.“ Common characteristic of these chapters is lack of interest in themes which are associated with the Confucian tradition of the Han. On the other side, “Huang-Lao chapters” differ mutually in terms of viewpoint, style etc. This raises a number of questions and controversies regarding the authenticity, dating and ideological and historical background of this text unit. These unsettled issues will be reflected in analysis of linguistic features and doctrinal content of the chapter 20 of "The Luxuriant Dew of the Spring and Autumn Annals".
ENG